2021
DOI: 10.1111/iwj.13615
|View full text |Cite
|
Sign up to set email alerts
|

Skin substitutes with noncultured autologous skin cell suspension heal porcine full‐thickness wounds in a one‐stage procedure

Abstract: Clinical application of skin substitute is typically a two‐stage procedure with application of skin substitute matrix to the wound followed by engraftment of a split‐thickness skin graft (STSG). This two‐stage procedure requires multiple interventions, increasing the time until the wound is epithelialised. In this study, the feasibility of a one‐stage procedure by combining bioengineered collagen‐chondroitin‐6‐sulfate (DS1) or decellularised fetal bovine skin substitute (DS2) with autologous skin cell suspensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…The ability of FB and KC cells to self-assemble into distinct dermal and epidermal layers in-vivo in response to endogenous biological cues was observed over 21 d. This migration was corroborated by previous works where cultured KCs seeded onto the underside of a skin substitute were observed to migrate upwards through the dermal scaffold to form an epidermis in 2-3 weeks [82,83]. In a similar study conducted more recently, Damaraju et al [27] applied drops of ReCell™ to the underside of a skin substitute used to treat full-thickness porcine wounds. Epithelial hyperplasia (the presence of KCs migrating upwards through the dermis towards the epidermis) was resolved by 42 d and the union of products was again deemed promising as a POC treatment strategy.…”
Section: Cellular Componentssupporting
confidence: 79%
See 1 more Smart Citation
“…The ability of FB and KC cells to self-assemble into distinct dermal and epidermal layers in-vivo in response to endogenous biological cues was observed over 21 d. This migration was corroborated by previous works where cultured KCs seeded onto the underside of a skin substitute were observed to migrate upwards through the dermal scaffold to form an epidermis in 2-3 weeks [82,83]. In a similar study conducted more recently, Damaraju et al [27] applied drops of ReCell™ to the underside of a skin substitute used to treat full-thickness porcine wounds. Epithelial hyperplasia (the presence of KCs migrating upwards through the dermis towards the epidermis) was resolved by 42 d and the union of products was again deemed promising as a POC treatment strategy.…”
Section: Cellular Componentssupporting
confidence: 79%
“…Gaining significant traction in the clinic, ReCell™ (Avita Medical Ltd, Cambridge, England) is an autologous cell harvesting, processing and delivery device that involves spraying non-cultured epidermal cells onto a wound site as soon as 30 min from biopsy harvesting [25]. Although not indicated for the treatment of full-thickness wounds in its standalone form, in-vivo studies showed that when ReCell™ was combined with Integra ® , the self-organisation of autologous cells accelerated re-epithelialisation of full-thickness wounds and mitigated the need for a STSG procedure [26,27]. To date, this integration of products is perhaps nearest to the vision of an immediate, single-stage, graft-free treatment strategy for full-thickness wounds.…”
Section: Skin Substitute Productsmentioning
confidence: 99%
“…Our results reported more significant signs of repair than those reported in a study on the same biomodel using decellularized fetal bovine skin substitute with autologous skin cell suspension [ 69 ], indicating that the wound closed in approximately 42 days after treatment and according to the histological result, the immature epithelium and presence of inflammatory cells in the wound treated with decellularized skin substitute were observed at 28 days. Likewise, the skin repair potential of construct 1 and hADM described here was higher than similar strategies evaluated in different animal models [ 67 , 70 , 71 ].…”
Section: Discussionsupporting
confidence: 51%